2015
DOI: 10.1177/194008291500800213
|View full text |Cite
|
Sign up to set email alerts
|

Seed Dispersal of Vitex Glabrata and Prunus Ceylanica by Civets (Viverridae) in Pakke Tiger Reserve, North-East India: Spatial Patterns and Post-Dispersal Seed Fates

Abstract: Civets are considered potentially important seed dispersers in tropical forests of Asia, but relatively little is known about spatial patterns of dispersal and post-dispersal fates of civet-dispersed seeds. We explored these aspects of civet seed dispersal for two tree species Vitex glabrata (Lamiaceae), also known as smooth chaste tree and Prunus ceylanica (Rosaceae), in Pakke Tiger Reserve, a tropical forest reserve in northeast India. Pakke has five known species of viverrids: small Indian civet (Viverricul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 41 publications
4
21
0
Order By: Relevance
“…This assumption may affect the scenario of primate extirpation as described in the later subsection, but not in the scenario of all LBF extirpation. However, we assume that their effect is negligible in our simulations, because they rarely feed on typical primate fruits such as Nephelium melliferum in our plot (unpublished data) and frequently disperse seeds out of old-growth forest into disturbed areas 49,51,52 .…”
Section: Methodsmentioning
confidence: 99%
“…This assumption may affect the scenario of primate extirpation as described in the later subsection, but not in the scenario of all LBF extirpation. However, we assume that their effect is negligible in our simulations, because they rarely feed on typical primate fruits such as Nephelium melliferum in our plot (unpublished data) and frequently disperse seeds out of old-growth forest into disturbed areas 49,51,52 .…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, Chakravarthy and Ratnam (2015) found that while civets did disperse the seeds of Vitex glabrata and Prunus ceylanica , they carried them within 50 m of the parent trees and deposited them on multiple substrates. However, seeds deposited on fallen logs experienced higher predation and had lower seed viability than those on the forest floor (Chakravarthy & Ratnam, 2015).…”
Section: Quantity and Quality Of Seed Dispersalmentioning
confidence: 94%
“…as is evidenced by the germination of seedlings of these species in civet feces across different years and sites (Mudappa et al, 2010). In contrast, Chakravarthy and Ratnam (2015) found that while civets did disperse the seeds of Vitex glabrata and Prunus ceylanica, they carried them within 50 m of the parent trees and deposited them on multiple substrates.…”
Section: Civet (Carnivora; Viverridae)mentioning
confidence: 95%
“…Seed dispersal by carnivores influences the recruitment of various plant species in temperate forests (Koike et al, 2008) and tropical forests (Chakravarthy & Ratnam, 2015;Zhou et al, 2008), that is, the seeds dispersed by these types of mammals often lead to the establishment of plants (Howe & Miriti, 2000). However, data on dispersal by carnivores in other ecosystems such as temperate forests (TF) and dry tropical forests (DTF) are scarce (Godínez-Alvarez et al, 2007).…”
Section: Introductionmentioning
confidence: 99%